Effect of fall armyworm (Spodoptera frugiperda) damage on the yield of four maize cultivars in the Coastal Lowland and Western Highland of Cameroon - Clovis Bessong, Tanyi; Nkongho, Raymond N.; Nyaka, Aurelie N.; Okolle, Justin N.; Tening, Aaron S.; Ngosong, Christopher (European Journal of Applied Sciences, 2021)
Maize (Zea mays L.) production in Africa is threatened by the invasive fall armyworm – FAW (Spodoptera frugiperda), and information on its agro-ecological variation and adaptation of different maize cultivars is scarce. The effect FAW was assessed on three hybrid maize cultivars (PAN–12, PAN–53, CMS–8704) and one Landrace in two agro-ecological zones (Coastal Lowland and Western Highland) of Cameroon. Maize cultivars were not fully resistant to FAW feeding and differences occurred in infestation severity and damage incidence between hybrid cultivars and landrace, but no significant yield differences was recorded. FAW infestation severity (IS) and damage incidence (DI) differed (P<0.001) significantly between cultivars in each agro-ecological zone. The highest IS occurred in hybrid maize cultivars as compared to the Landrace. Maize DI differed between cultivars in the Coastal Lowland with the highest in hybrid PAN–12 and PAN–53 as compared to CMS–8704 and Landrace (P<0.001). For the Western Highland, the highest damage incidence occurred in hybrid PAN–53 with the lowest in Landrace (P<0.05). Maize yield differed (P<0.001) significantly across cultivars within each agro-ecological zone. Significantly (P<0.001) higher maize yield occurred in the Coastal Lowland (ranging from 4.2−5.5 tons/ha) as compared to the lowest in the western highland (ranging from 3.2−4.6 tons/ha). The highest yield occurred in PAN–12 and PAN–53 as compared to CMS–8704 and Landrace for each agro-ecological zone. Overall, maize yield could not be predicted from FAW damage since the maize hybrids PAN–12 and PAN–53 recorded the highest damage and the highest yield, which implies high cultivar-specific defensive and yield-producing traits than the effect of FAW damage.